Depiction of a two-armed Yogini - Temples of India Project Team (Jio Institute, 2024)
This is one of the many images of yoginis found at the site, hinting at a lost yogini temple compound. The placid expressions of this two-armed yogini seated in the lalitasana posture suggest her benevolent nature. Contextualizing this image with several other relevant images suggests a maturity of Shakti and tantric traditions at the site.